Role of direct mechanism in two-nucleon T=0 transfer reactions in light nuclei using the (Li 6,α) probe - Zamora, J.C.; Ferreira, J.L.; Barioni, A.; Cardozo, E.N.; Abriola, Daniel Hugo; Arazi, Andres; Assunção, M.; de Barbará, Ezequiel; Cardona, Maria Angelica; Guimarães, V.; Hojman, Daniel Leonardo; Martí, Guillermo Virginio; et al. (American Physical Society, 2022)
Fil: Zamora, J.C.. Universidade de Sao Paulo; Brasil